Muhammadiyah as a Model of Transformative Islam in Indonesia - Andri Moewashi Idharoel Haq; R.F. Bhanu Viktorahadi; Mochamad Ziaul Haq (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to examine Muhammadiyah as a contemporary social movement rooted in religion in Indonesia and to explore how its role and influence shape educational institutions. Employing a bibliographic review combined with interviews and supported by historical analysis, this research is grounded in a sociological framework. Through this approach, the presence of Muhammadiyah can be examined scientifically using the perspective of new social movement theory, particularly through resource mobilization theory and identity-based theory. The findings indicate that both theoretical approaches are applicable, with identity-oriented theory taking precedence, followed by resource mobilization analysis. Muhammadiyah is portrayed as an organization that introduces a transformative model within Indonesia’s religiously inspired social movements. Within the framework of identity-oriented theory, Muhammadiyah represents both a collective identity and an ideological foundation. Meanwhile, resource mobilization theory highlights how Islam and Muhammadiyah function as platforms for mobilizing organizational resources, with the primary support originating from its members. Practically, this mobilization is reflected in philanthropic initiatives and the empowerment of Muhammadiyah’s charitable institutions. Previous scholarly works are reaffirmed in this study, demonstrating that Muhammadiyah, as a major Islamic movement, has made a significant contribution to shaping Indonesian society into a more educated and socially conscious community. For this reason, Muhammadiyah can be regarded as a transformative Islamic movement. Ultimately, this article contributes to the discourse on modernist Islamic thought, particularly within the framework of tajdid or Islamic renewal.